2015
DOI: 10.1186/s12943-015-0450-x
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate inhibits pro-proliferative miR-92a by diminishing c-Myc-induced miR-17-92a cluster transcription in human colon cancer cells

Abstract: BackgroundCompromised colonic butyrate production resulting from low dietary fiber or altered gut microbiota may promote colon neoplasia. Previous reports indicate these actions are mediated in part by altered levels of miRNAs, including suppressed expression of the oncogenic miR-17-92a cluster. Here, we sought to identify the mechanisms underlying these effects of butyrate in colon cancer.MethodsmiR-92a levels were measured in archived human colon cancer and adjacent normal colon specimens by microarray and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(128 citation statements)
references
References 53 publications
3
123
1
1
Order By: Relevance
“…SCFAs mainly include acetate, propionate and butyrate, and have anti‐inflammatory and antineoplastic properties, particularly butyrate, which is the preferred energy source for colonocytes . Related clinical studies revealed that patients with advanced CRC had diminished butyrate‐producing bacteria and lower levels of SCFAs when compared with healthy controls . Our study showed that the abundance of SCFAs‐producing bacteria ( Roseburia , Barnesiella , Lachnospiraceae bacterium‐A4 and Lachnospiraceae bacterium‐COE1 ) was reduced in HFD group.…”
Section: Discussionmentioning
confidence: 49%
“…SCFAs mainly include acetate, propionate and butyrate, and have anti‐inflammatory and antineoplastic properties, particularly butyrate, which is the preferred energy source for colonocytes . Related clinical studies revealed that patients with advanced CRC had diminished butyrate‐producing bacteria and lower levels of SCFAs when compared with healthy controls . Our study showed that the abundance of SCFAs‐producing bacteria ( Roseburia , Barnesiella , Lachnospiraceae bacterium‐A4 and Lachnospiraceae bacterium‐COE1 ) was reduced in HFD group.…”
Section: Discussionmentioning
confidence: 49%
“…In addition, the same group of researchers demonstrated that in vivo supplementation of a high red meat diet (300 g/day lean red meat) with butylated resistant starch (40 g/day butylated high amylose maize starch), restored miR-17-92 levels to baseline, thus miR-21 remained unchanged [79]. Recently, a novel mechanism of butyrate able to induce apoptosis and decrease proliferation was described [150]. Along with miR-17-29 down-regulation previously described, Hu et al demonstrated that butyrate decreases c-myc and increases p57 expression in colon cancer cells.…”
Section: Bioactive Dietary Components and Mirnamentioning
confidence: 99%
“…miRNAs regulate the expression of thousands of genes by inhibiting their expression and, consequently, have effects on many biological processes including those involved in tumorigenesis . Abnormal expression of miRNAs is implicated in the pathogenesis of CRC, where it is associated with disease progression, treatment response, and prognosis .…”
Section: Discussionmentioning
confidence: 99%